Overview on Cigarettes and Other Tobacco Products Act and its implementation: current update - Thakore, Dhwanit; Chavda, Mahesh; Parmar, Girish; Sheth, Tejal (International Journal Of Community Medicine And Public Health, 2020)
Tobacco use- a major public health issue in India has an enormous effect on the lower SES population. . There is an evident link between tobacco use or consumption and poverty. The widespread use of almost all forms of tobacco among the Indian population can be attributed to the social and cultural acceptance in the country. Cigarette and Other Tobacco Products Act, 2003 (COTPA) is the legislation that regulates tobacco in India. The prime objective of this review is to compile the literature with information about the laws regulating tobacco use and the status of implementation of tobacco control provisions covered under COTPA. Since effective tobacco control measures involve multi-stakeholders i.e public health, law, trade and commerce, industry, consumer, human rights and child development, coordinated efforts are required to successful enforcement. The outcome of the current literature is bridging the gaps to make the tobacco control a very important public health goal and thereby protect the population from the consequent morbidity and mortality due to tobacco use.